Effects of exercise training on metabolic syndrome risk factors in post-menopausal women – A systematic review and meta-analysis of randomised controlled trials - Becky Thomas (Clinical Nutrition, 2023)
Background & AimsAlterations in the hormonal profiles as women transition to the menopause predisposes individuals to the metabolic syndrome (MetS). In post-menopausal women, this can be exacerbated by sedentary behaviour and physical inactivity. Physical activity can convey many health benefits including improvement in MetS risk factors. However, it remains to be elucidated how differing exercise intensities and its mode of delivery can ameliorate MetS risk factors and resultant progression amongst post-menopausal women. The purpose of this systematic review and meta-analysis was to investigate the effects and efficacy of exercise training on MetS risk factors in post-menopausal women.MethodsDatabase searches using PubMed, Scopus, Web of Science and the Cochrane Central Register of Controlled Trials were conducted from inception to December 2021 for randomised controlled studies (RCTs) investigating exercise training (>8 weeks) in at least one of the MetS risk factors in post-menopausal women. Utilising the random-effects model, appropriate standardised mean differences (SMD) or mean differences (MD) with 95% confidence interval (CI) for each MetS risk factor were used to calculate the overall effect size between the exercise and control groups. Sub-group analyses were performed for exercise intensity, modality, and duration for each risk factor. Meta-regression was performed for categorical (health status) and continuous (body mass index) covariates.Results39 RCTs (40 studies) involving 2,132 participants were identified as eligible. Overall, the meta-analysis shows that exercise training significantly improved all MetS risk factors: waist circumference (WC) [MD: -2.61 cm; 95% CI: -3.39 to -1.86 cm; p < 0.001; 21 studies]; triglycerides (TG) [SMD: -0.40 mmol/L; 95% CI: -0.71 to -0.09 mmol/L; p = 0.01; 25 studies]; high-density lipoprotein (HDL) [SMD: 0.84 mmol/L; (95% CI: 0.41 to 1.27 mmol/L; p < 0.001; 26 studies]; fasting glucose (BG) [SMD: -0.38 mmol/L (95% CI: -0.60 to -0.16 mmol/L; p < 0.001; 20 studies]; systolic blood pressure (SBP) [MD: -5.95 mmHg (95% CI: -7.98 to -3.92 mmHg; p < 0.001; 23 studies]; and diastolic blood pressure (DBP) [MD: -4.14 mmHg (95% CI: -6.19 to -2.08 mmHg; p < 0.001; 23 studies]. Furthermore, sub-group analyses identified that moderate intensity and combined exercise training significantly improved MetS risk factors (p < 0.05) except for HDL, with combined exercise being the most effective. Long duration (≥12 weeks) training also significantly improved MetS risk factors except for TG. Meta-regression revealed no moderating effects on any MetS risk variables.ConclusionThis study reinforces the importance of regular physical activity as a non-pharmacological tool in the reduction of MetS risk in post-menopausal women, with significant metabolic improvements seen in interventions spanning 8 – 10 weeks. Moderate intensity and combined training significantly benefitted abdominal obesity, dyslipidaemia, dysglycaemia and hypertension in post-menopausal women. Improvements in at least one MetS risk were also seen with other exercise modalities and intensities.